2017
DOI: 10.1111/jne.12550
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal maternal separation opposes the facilitatory effect of castration on the respiratory response to hypercapnia of the adult male rat: Evidence for the involvement of the medial amygdala

Abstract: Respiratory manifestations of panic disorder (PD) include a greater respiratory instability and enhanced responsiveness to CO compared to normal individuals. Although the prevalence of PD is approximately three times greater in women compared to men, the origins of this sexual dimorphism remain poorly understood. Similar to PD patients, adult female rats previously subjected to neonatal maternal separation (NMS) show an increase in their ventilatory response to CO . Because this effect of NMS is not observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…In rats exposed to 10% CO 2 , the medial and central amygdala show increased c-Fos expression. This increase is associated with augmented minute ventilation, breathing frequency, and tidal volume 63 . Johnson et al 64 found that rats exposed to the 20% CO 2 challenge tended to increase c-Fos expression in the central amygdala, and this increase was related to increased fecal boli production (indicative of fear and anxiety) and thigmotaxis in the open field tests, but no effect of hypercapnia on c-Fos expression was detected in the medial and basolateral amygdala.…”
Section: Neurobiological Responsesmentioning
confidence: 95%
See 2 more Smart Citations
“…In rats exposed to 10% CO 2 , the medial and central amygdala show increased c-Fos expression. This increase is associated with augmented minute ventilation, breathing frequency, and tidal volume 63 . Johnson et al 64 found that rats exposed to the 20% CO 2 challenge tended to increase c-Fos expression in the central amygdala, and this increase was related to increased fecal boli production (indicative of fear and anxiety) and thigmotaxis in the open field tests, but no effect of hypercapnia on c-Fos expression was detected in the medial and basolateral amygdala.…”
Section: Neurobiological Responsesmentioning
confidence: 95%
“…The dorsomedial region of hypothalamus (DMH) is involved in the execution of behavior responses to aversive stimuli 73,74 . One study reported that rats exposed to 10% CO 2 did not differ from controls in the number of labeled cells on the DMH 63 . However, other studies have found that the DMH shows high c-Fos expression in rats exposed to 5% CO 2 and the 20% CO 2 challenge 30,64,70 , particularly in orexin neurons 34 found only in the DMH and perifornical nucleus of the hypothalamus 75 .…”
Section: Neurobiological Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this issue, one of the most convincing evaluation methods is an analysis of c-Fos expression, a product of the immediate-early gene c-fos , which is expressed in an activity-dependent manner [ 50 ]. Via this approach, many pieces of evidence have shown that MS stimulates various brain regions in different ways depending on the timing and duration of MS [ 51 , 52 ]. The current authors previously examined c-Fos expression after MS, mainly focusing on the hypothalamus and limbic brain regions, and demonstrated that repeated MS and a single incidence of MS during different developmental stages and periods showed different patterns of c-Fos expression [ 46 , 53 ].…”
Section: Brain Regions Activated During Msmentioning
confidence: 99%
“…The NMS protocol was identical to the one used in our previous studies 29,30 . Briefly, virgin females were mated and 3 days after delivery, each litter was separated daily from their mother 3 h/day (09:00-12:00) from postnatal day 3-12.…”
Section: Neonatal Maternal Separation (Nms)mentioning
confidence: 99%